The sensegiving role of advisors in farmer decision-making - M.T. Hayden; R. Mattimoe; L. Jack (Irish Journal of Agricultural and Food Research, 2023)
In Ireland, and in several other countries around the world, a situation of economic vulnerability exists for many farmers. Alongside this economic vulnerability, the farm management literature acknowledges that most farmers spend little time on financial management. In this context, we argue that farm advisory services have the potential to add value to the farming community by assisting farmers to make informed financial decisions, to combat these economic challenges. In this study, the role of professional advisors in the strategic financial decision-making process of farmers is explored to develop an understanding of how farmers avail of advice from, and interact with, farm advisors. A qualitative research approach of 27 semi-structured interviews and a focus group is adopted to explore the strategic financial decision-making process of farmers. The application of sensemaking theory helps us understand how advisors provide a sensegiving role in the farmer’s decision-making process. The evidence gathered identifies numerous professional advice sources that provide this sensegiving role in the strategic financial decision-making process of farmers but contends that two sources, accountants and agricultural consultants, appear most prominent. This study also reveals that the use of specific advice sources is strongly influenced by the type of strategic decision undertaken and the farm type in operation. The results provide an opportunity for policymakers, and those who provide advisory services to farmers, to reflect on how best to create an environment where farmers and farm advisors can work together, to develop sustainable farm enterprises which can contribute to rural development.